(untitled) (International Journal of Fine, Performing and Visual Arts, ISSN: 3006-6581, 2021)
The evolution of Indian cinema has been a fascinating journey intertwined with the dynamic socio-cultural fabric of the nation. This paper delves into the historical progression of Indian cinema, exploring its transformative phases and the profound impact it has had on the society it reflects. From its nascent days in the early 20th century to the vibrant cinematic landscape of the present, Indian cinema has mirrored the diverse cultural, social, and political shifts that have shaped the nation. The socio-cultural perspective adopted in this study unveils the symbiotic relationship between cinema and society. Indian cinema, often considered a mirror reflecting societal norms, has been a powerful agent of change, contributing to the shaping of collective identities and fostering a sense of cultural pride. The paper analyzes how themes, narratives, and characters in Indian films have evolved to echo the changing attitudes towards gender, caste, religion, and other societal constructs.